Active treatment of acidic mine water to minimize environmental impacts in a densely populated downstream area. (10th February 2019) - Qin, Junhao; Cui, Xiaoying; Yan, Hua; Lu, Wenzhou; Lin, Chuxia
Abstract: Field monitoring was conducted to evaluate the effects of active mine water treatment on improving the water quality of receiving river in a densely populated catchment. Microcosm experiment was also performed to assess the effects of treated mine water on the growth of the vegetable and the uptake of trace elements by the vegetable. The results show that the treatment process was very effective in terms of raising the water pH (from below 3 to above 8 at the high-flow event) and removing trace elements (over 99% for most of the investigated trace elements) from the mine water. However, overdose of acid neutralizing materials might occur during low- and medium-flowing period, resulting in unacceptable high pH in the river reach immediately downstream of the treatment facility. To improve the treatment performance, more accurate estimation of lime requirement for treating the mine water can be done by a real-time monitoring for titratable acidity of mine water in the buffer pond to guide lime-dosing. It was found that downstream transport of trace elements still took place, especially for elements with variable valency such as manganese and chromium. The addition of lime also caused elevated concentration of barium and strontium in the river water, which requires assessment of their potential ecotoxicity to the downstream aquatic ecosystem. The use of treated mine water for irrigation purpose has both advantages and disadvantages; while it served as a source of irrigation water and tended to reduce the uptake of arsenic by the crop plant, the acid materials could still be introduced into the soils with the irrigation water and adversely affected the growth of the vegetable. It could increase the leaching of some trace elements especially arsenic from the soil to the shallow aquifer and cause contamination of groundwater. Highlights: Mine water treatment minimized environmental impacts in a densely populated area. Unacceptable high pH due to lime overdosing during low- and medium-flowing period. Downstream transport of trace elements especially Mn, Cr, Ba and Sr still took place. Treated mine water as an irrigation water source has advantages and disadvantages. Suggestions to improve treatment process and assessment of environmental risk.